Selenium and Neurological Diseases: Focus on Peripheral Pain and TRP Channels - Nazıroğlu, Mustafa; Öz, Ahmi; Yıldızhan, Kenan (Current Neuropharmacology, 2020)
Pain is a complex physiological process that includes many components. Growing evidence supports the idea that oxidative stress and Ca2+ signaling pathways participate in pain detection by neurons. The main source of endogenous reactive oxygen species (ROS) is mitochondrial dysfunction induced by membrane depolarization, which is in turn caused by Ca2+ influx into the cytosol of neurons. ROS are controlled by antioxidants, including selenium. Selenium plays an important role in the nervous system, including the brain, where it acts as a cofactor for glutathione peroxidase and is incorporated into selenoproteins involved in antioxidant defenses. It has neuroprotective effects through modulation of excessive ROS production, inflammation, and Ca2+ overload in several diseases, including inflammatory pain, hypersensitivity, allodynia, diabetic neuropathic pain, and nociceptive pain. Ca2+ entry across membranes is mediated by different channels, including transient receptor potential (TRP) channels, some of which (e.g., TRPA1, TRPM2, TRPV1, and TRPV4) can be activated by oxidative stress and have a role in the induction of peripheral pain. The results of recent studies indicate the modulator roles of selenium in peripheral pain through inhibition of TRP channels in the dorsal root ganglia of experimental animals. This review summarizes the protective role of selenium in TRP channel regulation, Ca2+ signaling, apoptosis, and mitochondrial oxidative stress in peripheral pain induction.
Keywords: peripheral pain